Evidence of Levallois strategies on cores at Guanyindong cave, Southwest China during the Late Middle Pleistocene. (February 2023) - Hu, Yue; Marwick, Ben; Lu, Hongliang; Hou, Yamei; Huang, Weiwen; Li, Bo
Highlights: Specific techno-typological analysis on Levallois assemblage at LMP site in China. Inter-site comparisons between Guanyindong and African, European Levallois assemblages. Confirm the earliest Levallois concept in East Asia. Abstract: The discovery of early Levallois stone-tool technology at 170 ka at Guanyindong cave, Southwest China, has raised questions about the validity and characters of Levallois strategy at this site. To address these questions, we present a detailed technological analysis that primarily focuses on the Levallois cores, along with Levallois flakes and by-products. These analysis include analytical descriptions, technological illustrations, worldwide inter-site comparisons, and quantitative analysis, providing extended and substantial evidence of the usage of Levallois strategy at Guanyindong cave, and indicating highly technological variability and likely convergent technological evolution during Late Middle Pleistocene in East Asia.